Indonesian Muslim in the Netherlands: Responding to Nationalism, Islamism, Democracy, and Pluralism - Dzuriyatun Toyibah (UIN Sunan Gunung Djati Bandung, 2022)
There are very few studies relating to the practice of Indonesian Islam in the Netherlands, and how Indonesian Muslims in the Netherlands respond to a number of citizenship issues (such as nationalism, Islamism, democracy and pluralism). This article describes quantitative data based on survey results to understand practice of Indonesian Islam in the Netherlands, and to describe the responses of Indonesian Muslims in the Netherlands to a number of citizenship issues. The survey covers demographic information, the practice of Indonesian Islam, responses about several topics such as Indonesia, nationalism and Islam; Islamism, democracy and pluralism, and participation in Islamic organizations. The survey involved 89 respondents living in the Netherlands in 2017. The findings show that rituals associated to Nahdlatul Ulama (the biggest Islamic organization in Indonesia) are most common among the Indonesian community in the Netherlands. In general, respondents are strongly nationalists. However, some political Islam principles are becoming more commonplace among Indonesian Muslims in the Netherlands, which indicates that the support for Islamism is strong enough among them.